COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING DEVELOPMENT (MUSRENBANG) IN POLEJIWA VILLAGE, WEST MALANGKE DISTRICT, NORTH LUWU DISTRICT - Vera Amalia; Didin Halim; Novayanti Sopia Rukmana; Putri Dzakilla Handayani (Jurnal Aktor, 2026)
The aim of this research is to determine and describe community participation in the implementation of development planning (Musrenbang) and the factors that determine community participation in development planning deliberations in Polejiwa Village. The type of research used in this research is descriptive qualitative and the data collection methods used are interviews, observation and documentation. The data analysis techniques used are data condensation, data presentation, and verification or drawing conclusions. The research results show that the level of community participation in the implementation of development planning deliberations in Polejiwa Village is still less than optimal because generally the community is not directly involved in the development program planning process that will be implemented each year. Factors that determine success in the process of implementing development planning deliberations (musrenbang) in Polejiwa Village include community awareness, level of education, socialization, trust in the government, role of leaders, socio-economic conditions.